CHARACTERISTICS OF DUWET KARST SPRING BASED ON BASEFLOW INDEX ASSESSMENT AND ITS POTENTIAL IN FRESH WATER SUPPLY - Pipit wijayanti; Rita Noviani (GeoEco, 2021)
This study aims to determine the potential of Duwet springs and their availability for supplying fresh water to the surrounding community. we use hydrographs to analyze aquifer characteristics. To analyze the hydrographs, we use water level and spring discharge data. Automatic Water Level Record (AWLR) records water level data for 1 dry season and 1 rainy season every 15 minutes. We use the volumetric method to measure the spring discharge 14 times. We compare the base flow and demand over a year to analyze the potential for fresh water. The results show that the Stage discharge rating curve y = 0.0002e5,453x with R² value of 0.87. Duwet Springs is a perennial spring that has a small discharge (class VI). The largest discharge ever recorded was 0.69 L/s (March 7, 2020) and the smallest recorded was 0.12 L/s (August 21, 2020). BFI value varied between 0.05 and 1 with mean 0.801. The total base flow is 2490675.734 L (rainy season) and 1563419.873 L (dry season). These springs are sufficient for 75% of the rainy season and 84% in the dry season. This indicates that the existence of Duwet springs is very important for the surrounding community.